EKSISTENSI KESENIAN TANJIDOR DI KOTA PONTIANAK - Azhari, Imam; Ismunandar, Ismunandar; Silaban, Chiristianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractTanjidor is a kind of entertainment bersiafat artistry Betawi folk orchestra, which uses western musical instruments, especially wind instruments. Tanjidor originally developed from landhuis environment. This art entered West Kalimantan around the 16th century through the trade at the time. This art is played to enliven a variety of events such as weddings, circumcisions, and events such as birthdays governance Pontianak. This study was to determine objectively clarity about the arts tanjior in Pontianak. The method used in this research is descriptive. Forms of research used in this research is a form of qualitative research. The research subjects were the players Tanjidor in Pontianak. The results showed that the presence of musical arts tanjdor in Pontianak is as follows: factors that encourage the existence of musical arts tanjidor in Pontianak is factor artist changes in the society Factors inhibiting presence tanjidor musical arts in Pontianak is The element of art dating from the West. Changes in agrarian society to industrial. Measures to overcome barriers to the existence of musical arts tanjidor in Pontianak Regarding the readiness of the Indonesian nation in the face of modernization.) Music tanjidor in Pontianak City is in need of Pontianak City.Keywords: Existence, MusikTanjidorÂ